Teacher Training and Professional Development in Early Childhood Education: Global Trends and Challenges - Fina Fadila; Riska Ayu Saputri (International Journal of Educational Development, 2024)
This paper explores global trends in teacher training and professional development for early childhood educators. By examining policies and practices from various countries, the study identifies common challenges in the field, including insufficient funding, lack of standardized training frameworks, and limited access to ongoing professional development. The findings suggest that investing in teacher training and lifelong learning opportunities is critical to enhance the quality of early childhood education and bridge skills gaps among educators.